Managing the adolescent athlete with Type 1 Diabetes Mellitus - Draznin, M. B. (Pediatric Clinics of North America, 2010)
Providing safe and successful diabetes management assistance and advice to an adolescent athlete is a challenging task. It should also be a rewarding task. To make accurate and useful recommendations one must gain knowledge about the athlete, the sport, the interaction of exercise and diabetes, and supporting resources. This article points to sources of information and illustrates the use of some of them.